1988
DOI: 10.1111/j.2044-835x.1988.tb01078.x
|View full text |Cite
|
Sign up to set email alerts
|

The perception of faces in different poses by 1‐month‐olds

Abstract: An experiment is described in which the ability of 1‐month‐old infants to recognize their mothers visually was explored with the live faces of mother and stranger presented in three different poses. The en face and half‐profile poses resulted in significant visual preferences for the mother being demonstrated, but the profile pose did not. The temporal stability of the observed memory is discussed along with potential methodological artifacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Note: A comment made by an anonymous reviewer concerns the use of related t-tests in present studies and in our previous research (Sai and Bushnell, 1988;Bushnell et al, 1989;Sai, 1990). The data have been analysed again using singlesample t tests as suggested by the reviewer, and significant results were obtained, as is the case in the present studies.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Note: A comment made by an anonymous reviewer concerns the use of related t-tests in present studies and in our previous research (Sai and Bushnell, 1988;Bushnell et al, 1989;Sai, 1990). The data have been analysed again using singlesample t tests as suggested by the reviewer, and significant results were obtained, as is the case in the present studies.…”
Section: Discussionmentioning
confidence: 91%
“…In our previous testing (Sai, 1990;Bushnell et al, 1989;Sai and Bushnell, 1988), the newborn infants showed a number of head turns towards the stimulus faces. Such activity disappeared along with the control of the mother's voice in Exp.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Even newborns preferred a still image of the mother's face over that of a female stranger (Walton, Bower, & Bower, 1992). When presented with dynamic or live faces, neonates and infants during the first month are able to discriminate the mother from a female stranger (e.g., Carpenter, Teece, Stechler, & Friedman, 1970;Field, Cohen, Garcia, & Greenberg, 1984;Sai & Bushnell, 1988). By 4-7 months, babies show discrimination among different facial expressions (Biringen, 1987;Caron, Caron, & MacLean, 1988;Kestenbaum & Nelson, 1990;Nelson & Horowitz, 1983), and perhaps even at birth (Field et al, 1983).…”
Section: Introductionmentioning
confidence: 97%
“…First, the caregiver shifts gaze, then the robot observes the caregiver's face or a spot on the table as the current target, obtaining information about S f , where the caregiver appears to be looking, or S o , what objects are being observed. We assume that the robot prefers both the caregiver's full face and salient objects to the caregiver's profile because infants appear to prefer the full human face [11] and objects with complex textures or symmetrical patterns [12]. The robot has reward variables representing such preferences.…”
Section: A Environment and Interactions Between Caregiver And Robot mentioning
confidence: 99%